Zbed3 promotes proliferation and invasion of lung cancer partly through regulating the function of Axin‐Gsk3β complex. Issue 2 (12th November 2018) - Shi, Xiuying; Zhao, Yang; Fan, Chuifeng
Abstract: Our previous work showed that Zbed3 is overexpressed in nonsmall cell lung cancer and that down‐regulation of Zbed3 inhibited β‐catenin expression and cancer cell proliferation and invasiveness. Here, we investigated Zbed3's ability to promote lung cancer cell proliferation and invasion and the involvement of the Axin/TPC/glycogen synthase kinase 3β (Gsk‐3β) complex to the response. Coimmunoprecipitation assays showed that wild‐type Zbed3 bound to Axin but a Zbed3 mutant lacking the Axin binding site did not. In A549 and H1299 lung cancer cells, Zbed3 overexpression promoted cancer cell proliferation and invasiveness, as well as Wnt signalling and expression of downstream mediators, including β‐catenin, cyclin D1 and MMP7 ( P  < 0.05). In contrast, the Zbed3 mutant failed to enhance β‐catenin expression ( P  > 0.05), and its ability to promote cancer cell proliferation and invasiveness was much less than wild‐type Zbed3 ( P  < 0.05). The ability of Zbed3 to increase β‐catenin levels was abolished by Axin knockdown in A549 cells ( P  > 0.05). Similarly, treating the cells with a GSK‐3β inhibitor abolished Zbed3's ability to increase β‐catenin levels and Wnt signalling. These results indicate that Zbed3 enhances lung cancer cell proliferation and invasiveness at least in part by inhibiting Axin/adenomatous polyposis coli/GSK‐3β‐mediated negative regulation of β‐catenin levels.